Pendapat Generasi Muda terhadap Pelestarian Budaya Feng Shui Secara Berkelanjutan - Yap, Julina (Indonesian Character Journal, 2024)
The importance of preserving traditional Chinese culture in Indonesia and the declining understanding of traditional Chinese culture among young Chinese Indonesians in the modern era have prompted the author to investigate the perspectives of young Chinese Indonesians towards one aspect of traditional Chinese culture, namely Feng Shui. The respondents of this study comprised 35 individuals of Chinese descent. Data collection was conducted using questionnaires distributed through Google Forms. The respondents were members of Generation Z, aged between 12 and 27 years. The conclusion of this study indicates that one of the dominant factors influencing young Chinese Indonesians to believe in and practice Feng Shui is family tradition. Conversely, the factors that lead young Chinese Indonesians to disbelieve in and not practice Feng Shui are its perceived inconsistency with logical reasoning and the influence of religion. A recommendation for future research is to include a more diverse range of respondents from Generation X and the millennial generation, in order to map out the differences in perspectives across generations and their underlying causes. Keywords: Feng shui, generation z, family tradition, religion Â  Pentingnya pelestarian kebudayaan tradisional Tionghoa di Indonesia, dan semakin rendahnya pemahaman generasi muda Tionghoa Indonesia tentang kebudayaan tradisional Tionghoa di era modern ini, mendorong penulis untuk meneliti tentang pandangan generasi muda Tionghoa Indonesia terhadap salah satu budaya tradisional Tionghoa, yaitu Feng Shui. Responden dari penelitan ini adalah sebanyak 35 orang keturunan Tionghoa. Pengumpulan data dilakukan berdasarkan hasil pengisian kuesioner dalam bentuk Google Form. Responden penelitian adalah generasi Z yang berusia 12 sampai 27 tahun. Kesimpulan dari penelitan ini adalah salah satu faktor dominan yang mempengaruhi generasi muda Tionghoa Indonesia untuk percaya dan menerapkan budaya Feng Shui adalah karena tradisi keluarga. Sedangkan factor yang mempengaruhi generasi muda Tionghoa Indonesia untuk tidak percaya dan tidak menerapkan budaya Feng Shui adalah karena dinilai tidak sesuai dengan logika berpikir dan pengaruh agama. Saran untuk penelitian selanjutnya adalah responden penelitian lebih bervariasi dari generasi X dan generasi milenial, sehingga dapat dipetakan perbedaan pandangan dari setiap generasi dan faktor penyebabnya. Kata kunci:Feng Shui, Generasi Z, tradisi keluarga, agama